ПІДВИЩЕННЯ ЕФЕКТИВНОСТІ АЛГОРИТМІЧНОГО ЗАБЕЗПЕЧЕННЯ ПОБУДОВИ ДИСКРЕТНИХ МАКРОМОДЕЛЕЙ ТА ЇХНЯ АДАПТАЦІЯ ДО ПРОГРАМ РОЗРАХУНКУ ЕЛЕКТРИЧНИХ КІЛ - Гоголюк, О.П.; Козак, Ю.Я.; Росоловскі, Є.; Стахів, П.Г. (Інститут електродинаміки НАН України, Київ, 2019)
In the paper an improved algorithm for development of discrete macromodels describing technical system components of different nature, including electrical, using the expert analysis, parallel calculations and evolution technique is proposed. The algorithm makes it possible to reduce computational complexity of the macromodels creation essentially. The possibilities of the proposed algorithm adaptation to computer programs for electrical systems simulation which components are discrete macromodels were discussed. References 8, figure 1.